SportsWars : athletes in the age of Aquarius - Zang, David (University of Arkansas Press, 2001)
"The Vietnam era's tensions - between tradition and new possibilities, black and white, young and old, male and female - were played out on the field of professional and organized sports. Sports Wars shows that the century-old position of sports as the standard-bearer for American values, and as a central way of building character, made it a prime target in this time of general disenchantment. Critics began to challenge not only individual abuses but sport's very ideals, and for the first time these critics included athletes themselves. Zang locates a variety of larger cultural debates within professional sports and organized sports more generally: changing valuations of hard work and the physical, winning versus character, and challenges to authority. He also considers the relationships between sports and other domains of popular culture, including the counterculture, rock and roll, and Hollywood."--BOOK JACKET.